Do Finnish work integration enterprises benefit the community?. (1st December 2017) - ,; ,; ,; ,
Abstract : This study explores Finnish work integration social enterprises through social enterprise criteria identified in previous research, notably the aim to benefit the community. Previous research has identified positive motivations in social enterprises, but whether these are played out in practice is less examined. This study makes a contribution by exploring the situation in Finland, where social enterprises are still a relatively new phenomenon as compared with many other countries. In this study, in light of the interviews, a strong commitment among social enterprise managers to serving the community and specific people is revealed. This may be achieved by providing viable employment opportunities and avenues for participation, for instance. However, the findings also indicate many challenges, obstacles and even threats faced by the studied social enterprises. These affect opportunities to realise these enterprises' whole potential.